Regulation of STK38 by autophagy governs YAP1 activity during paligenosis - Yongji Zeng; Yang-Zhe Huang; Qing Kay Li; Raymond Ho; Steven J. Bark; Spencer G. Willet; Richard J. DiPaolo; Jason C. Mills (Proceedings of the National Academy of Sciences, 2026)
Paligenosis is a conserved cellular plasticity program that allows mature cells to reenter the cell cycle in response to tissue injury. Paligenosis progresses via three stages: autodegradation (with dramatic increase in autophagy and lysosomes), induction of metaplastic or fetal-like genes, and cell cycle entry. Hippo signaling, particularly the downstream effector YAP1, regulates cellular plasticity, but its role in paligenosis has not been studied. Here, we examine YAP1 dynamics during paligenosis in digestive-enzyme-secreting chief cells from the mouse stomach. We identified Serine/Threonine Kinase 38 (STK38) as a noncanonical YAP1 kinase that phosphorylates and deactivates YAP1 in uninjured chief cells. During paligenosis, STK38 was degraded by autophagy in stage 1, dephosphorylating and activating YAP1. YAP1 activation was necessary and sufficient for paligenosis-driven conversion of chief cells into metaplastic, proliferating progenitors. Additionally, we show that STK38, like canonical Hippo kinases, interacts with Neurofibromatosis Type 2 (Merlin), a scaffold that recruits Hippo kinases to phosphorylate YAP1. We also observed the same pattern of YAP1 induction via autophagic destruction of STK38 in other tissues and cell types, suggesting injury-induced activation of autophagy in differentiated cells during tissue damage may be a more general feature by which Hippo effectors induce plasticity for regeneration.